Ecological interactions mediate projected loss of kelp biomass under climate change. (16th December 2021) - Davis, Tom R.; Champion, Curtis; Coleman, Melinda A.
Abstract: Aim: Climate change has precipitated loss of kelp in temperate regions globally, with further losses projected in response to ocean warming. Projected climate‐driven changes to kelp are commonly derived from responses to sea surface temperature and neglect the effects of important ecological interactions, such as herbivory. Here, we use a stacked species distribution model to project impacts of future climate scenarios on kelp distribution and biomass incorporating the effects of key ecological interactions. Location: The eastern Australian coastline (28.0–37.5°S). Methods: A stacked species distribution model, incorporating ecological interactions with urchins, was used to project future effects of climate change on kelp. This model incorporated key drivers of kelp occurrence and cover (habitat availability, light and in situ temperatures) that are rarely considered when projecting the effects of climate change on kelp. Results: Consistent with previous research, we find range contractions of kelp ( 275 km) at lower latitudes (<32°S), due to ocean warming under RCP 8.5 ( 3.4°C) by 2100. However, in contrast to previous studies, we find range contractions will not occur under RCP 2.6 ( 0.8°C), and only moderate contractions are projected ( 55 km) under RCP 6.0 ( 2.3°C). Instead, vertical migration of kelp, from shallow areas to cooler deep water refugia, is likely under future change. Interestingly, range contractions at lower latitudes are projected to be offset by increased kelp biomass at higher latitudes (32–37.5°S) resulting from reductions in urchin herbivory. Consequently, a net gain in kelp biomass is projected for mainland eastern Australia by 2100 under RCPs 2.6 and 6.0 (up to 29.4%), while relatively small net losses are projected under RCP 8.5 (−3.5%). Main conclusions: Considering key ecological interactions when developing species distribution models can significantly change projections of habitat loss and must be integrated into assessments to accurately evaluate future change and enable evidence‐based management.